Nilai-Nilai Moderasi Beragama dalam Buku Ajar Pendidikan Agama Islam dan Budi Pekerti Kelas IV Sekolah Dasar Kurikulum Merdeka Belajar - Muhamad Alfi'an Arrofi; Khojir Khojir (Journal on Education, 2024)
The spread of radicalism has occurred massively in various lines of life, this encourages the need for preventive action, namely by internalizing the value of religious moderation in students in schools. This study aims to analyze the value of moderation in grade 4 textbooks and describe the renewal of the independent curriculum book. The research was conducted using the library research method based on Content Analysis with data triangulation techniques, while the findings in this study showed that the values ​​of religious moderation had been integrated into all 10 chapters of teaching materials in Islamic religious education textbooks and manners for class 4 independent curriculum . The values ​​of moderation are Civilized (ta'addub), Exemplary (Qudwah), Citizenship and Nationality (Muwathanah), Taking the middle way (Tawasuth), Balanced (Tawazun), Straight and firm (I'tidal), Equality (Musawah ), Deliberation (Syura'), Tolerance (Tasamuh) and Dynamic and Innovative (Tathwur wa Ibtikar). What is contained in the various components is in the form of learning achievements (CP), learning objectives (TP), teaching materials, various strategies as well as evaluation and assessment of achievements. The conclusion is that the textbooks published by the independent curriculum contain more moderation values ​​than the previous curriculum.